Enbal Agribusiness Development Strategy in The Kei Islands, Southeast Maluku Regency - Timisela, Natelda R; Sari, Raja M; Tahitu, Florensya (International Journal of Scientific Research and Management (IJSRM), 2025)
Enbal plant is a mainstay commodity in Southeast Maluku Regency because it has been widely diversified into value-added and selling value products. They can anticipate future food insecurity, so it can be an alternative to support national food security, especially in Maluku. This study aims to find out the various internal and external factors that influence the development of Enbal agribusiness and formulate the Enbal agribusiness development strategy in Southeast Maluku Regency. The research was carried out in the Kei Kecil Islands, Southeast Maluku Regency. The research locations are in three villages/Ohoi, namely Kelanit, Wain, and Debut. The research location was chosen deliberately with a specific purpose (purposive sampling) because the people in these villages generally work as farmers and enbal processing. The sample in this study amounted to 30 people who were taken by the census, and seven experts from BaLitbang agencies, the Agriculture Service, and the Ohoi/Village Government were selected intentionally (purposive sampling). The data collection stage evaluates internal factors and external factors, which are formulated into a table of internal strategic factors or IFAS (Internal Strategic Factors Analysis Summary) and external strategy tables or EFAS (External Strategic Factors Analysis Summary).  The SWOT analysis results produce seven alternative strategies that can be applied in developing enbal agribusiness. The results of the QSPM analysis resulted in the right strategic priorities to be used in the development of agribusiness in Southeast Maluku Regency, namely the development of areas for processing enbal centers by increasing facilities both in terms of production and marketing to increase visitor engagement with a TAS (Total Attractive Score) value of 5.380.